The The Critique of Technocracy in Riga Stencil Graffiti - Skulte, Ilva; Kozlovs, Normunds (Information & Media, 2020)
The utilization of the street as an alternative and independent medium for transmission of radical political ideas is a form of civil disobedience manifested thus to a certain extent in a work of propaganda and is an example of creative idealism. In this case graffiti can be regarded as a non-violent protest that was theoretically described by Henry David Thoreau in the treatise on “The Duty of Civil disobedience”, a work that has become an essential part of anthologies of political and social philosophy. To a certain degree, in its visual format, graffiti is a continuation of the “samizdat” tradition dating back to the Soviet era, both in the sense of a socially critical message and in the use of an alternative medium. Proposing a new, tactical usage of technology critically directed against technocracy of contemporary society youth of the city is trying to occupy it’s public space by specific type of aesthetization and, in the same time, is delivering clear message. The goal of this paper is the reading and interpretation of messages of the images and texts in stencil – graffiti in Riga in the context of interplay between counter cultures, different minor social groups and their ideologies. The method used is social semiotic analysis. The results show that the criticism of technocratic capitalism, consumerism and the oppression of life and the nature are most important issues taken up by the authors of stencils.